Balanchine and the lost muse revolution and the making of a choreographer - Kendall, Elizabeth 1947- (Oxford Univ. Press, 2013)
"Balanchine and the Lost Muse" traces the early lives and friendship of famed choreographer George Balanchine and the extraordinary young ballerina Lidia (Lidochka) Ivanova, from the years just before the 1917 Russian Revolution to Balanchine's escape from Russia in 1924 -- and in the process, sheds new light on a crucial flash point in the histories both of modern ballet and of Russia itself.